The effect of dietary forage to concentrate ratio and forage type on milk phospholipids and fatty acid composition of polar lipids - Jaakamo, Mari J.; Luukkonen, Tytti J.; Kairenius, Piia K.; Bayat, Ali R.; Ahvenjärvi, Seppo A.; Vilkki, Johanna H.; Leskinen, Heidi M. (American Dairy Science Association, 2023)
The effects of grass silage and red clover silage on milk fatty acid (FA) composition are extensively studied, but little is known of their impacts on minor lipid constituents of milk fat globule membrane. We investigated the effects of forage:concentrate (FC) ratio in grass silage-based diets and forage type (grass silage vs. red clover silage) on selected molecular species of milk phospholipids (PL) and the FA composition of PL. Ten multiparous Nordic Red cows were offered following dietary treatments: grass silage-based diets containing 70:30 (HG) or 30:70 (LG) FC ratio or a red clover silage-based diet (RC) comprising 50:50 FC ratio on a dry matter basis. The most abundant molecular species within the phosphatidylcholines was 16:0–18:1 phosphatidylcholine that was increased by 18% in HG compared with LG milk. Dietary treatments did not affect the relative proportion of 18:1–18:1+18:0–18:2 phosphatidylethanolamine that was the most prevalent species (ca. 44–45%) in that class. We identified the d18:1–22:0 sphingomyelin as the most abundant sphingomyelin species that tended to increase in HG milk compared with LG. The FC ratio did not affect the relative proportions of saturated FA nor monounsaturated FA in PL, but the proportion of cis-9 18:1 was elevated in HG vs. LG milk, whereas the proportion of 18:2n-6 was 50% higher in LG vs. HG milk. The RC diet increased monounsaturated FA and 18:3n-3 levels in PL compared with grass silage-based diets and decreased the relative proportion of saturated FA. However, the RC diet did not affect the relative proportion of polyunsaturated FA in PL, although red clover silage typically increases the proportion of polyunsaturated FA in milk fat. This study provides valuable knowledge of the minor lipid components in milk on species level in relation to common feeding strategies in high-forage systems.
Keywords: grass silage; red clover silage; phospholipid; polar lipid; fatty acid composition